The SWOT Approach to Waste Bank Management Study Case Bangkitku Waste Bank: Pendekatan SWOT Pengelolaan Bank Sampah Studi Kasus Bank Sampah Bangkitku - Viareco, Hariestya; Adriansyah, Endi; Sufra, Rifqi (Jurnal Engineering, 2024)
The Waste Bank is an example of a strategy for obtaining direct economic benefits from waste and reducing environmental pollution, especially waste. The Bangkitku Waste Bank is one of the waste banks in Jambi where people saving money through waste collection that is grouped according to type. From the research results, it was found that the amount of waste saved on average each month was 216.49 kg of paper type, 32.9 kg of plastic type and 3.25 kg of aluminum, a total of 252.64 kg. SWOT analysis of waste management at the Bangkitku Waste Bank has yielded positive results. Apart from contributing to reducing waste generation, this activity can change behavior and help improve the community's economy.